IMPLEMENTASI KEBIJAKAN PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DI KECAMATAN KOMBI - Yulia ., Rantung; Agustinus ., Pati; Femmy ., Tulusan (Sam Ratulangi University, 2021)
This study aims to determine the implementation of Village Owned Enterprises (BUM Desa) management policies in Kombi District. The sampling technique used purposive sampling so that Kombi Village, Ranowangko Dua Village and Tulap Village were selected. The research method is descriptive with interviews, with data analysis, namely data reduction, data presentation and conclusion drawing.The results showed that the implementation of the Village Owned Enterprise Management Policy (BUM Desa) in Kombi District for communication indicators still found discrepancies, namely the transmission of information dissemination, besides that the clarity of information about each program was still very lacking and the information submitted related to the program was not carried out consistently and continuously by BUMDes in Kombi District.